Accuracy of Ultrasound Estimated Fetal Weight in Small for Gestational Age and Appropriate for Gestational Age Grown Periviable Neonates - Haragan, Adriane; Himes, Katherine (American Journal of Perinatology, 2018)
Objective Clinicians use estimated fetal weight (EFW) as a proxy for birth weight (BW) in the antenatal period. Our objective was to compare the accuracy of EFW obtained by ultrasound to BW among infants born during the periviable period and determine if accuracy of EFW varied among small for gestational age (SGA) versus appropriate for gestational age (AGA) grown neonates.Study Design We included women who delivered between 230/7 and 256/7 weeks' gestation and had an EFW within 7 days of delivery. Mean percentage difference and median absolute percentage difference between EFW and BW were calculated.Results Our cohort included 226 neonates with a mean gestational age of 241/7 ± 0.8 weeks and median BW of 653 g (interquartile range [IQR]: 580–750 g). The median absolute percentage difference between EFW and BW of fetal weight estimates was 9.2% (IQR: 3.6–17.2). EFW overestimated BW for 75% (n = 171) of the cohort. Among SGA infants, the mean percentage difference in EFW and BW was 16.2 ± 19.4% versus 6.9% ± 13.1% in AGA infants (p = 0.019).Conclusion EFW overestimated BW in this cohort. In addition, ultrasound was less accurate among infants born SGA. These data are important to consider when counseling families facing periviable delivery.
Keywords: periviable birth; preterm birth; estimated fetal weight; small for gestational age; ultrasound; accuracy of ultrasound; birth weight